2014
DOI: 10.1002/app.41234
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanomaterial‐based copolymer of styrene–divinylbenzene resins: Efficient interaction through graphene/CNTs polymer network

Abstract: Carbon nanotubes (CNTs) and graphene were separately incorporated into the cross‐linked network of styrene–divinylbenzene composites via in situ suspension polymerization. The prepared copolymers were first chloromethylated and then aminated with trimethylamine to obtain ion exchange resins (IERs). The CNTs‐based and graphene‐based composites exhibited good dispersion throughout the polymer matrix with strong interaction within the network. Remarkable enhancement in antiswelling properties and thermal stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Then PS-DVB-HC showed a major weight loss stage about 70%, which was due to the degradation of the branching chains and crosslinking networks to short chains or volatile compounds induced by oxidative atmosphere. 20,40,41 The third stage weight loss of 20% was assigned to the combustion of char residue of carbonaceous to volatile fragments (such as CO 2 and water), and all the samples completely burnt off at 600 C. In the case of GPNC-IERs, the last stage showed higher amount of char residue compared to the PS-DVB-HC, which was related to the decomposition/ combustion of graphene and the residue of carbonaceous. The extrapolated degradation onset temperatures (T d ) and the temperature of the maximum weight loss rate (T max1 and T max2 ) in Table 3 showed the effect of graphene content on the degradation behavior and thermal stability of the GPNC-IERs.…”
Section: Carbon While the G-bandmentioning
confidence: 99%
See 2 more Smart Citations
“…Then PS-DVB-HC showed a major weight loss stage about 70%, which was due to the degradation of the branching chains and crosslinking networks to short chains or volatile compounds induced by oxidative atmosphere. 20,40,41 The third stage weight loss of 20% was assigned to the combustion of char residue of carbonaceous to volatile fragments (such as CO 2 and water), and all the samples completely burnt off at 600 C. In the case of GPNC-IERs, the last stage showed higher amount of char residue compared to the PS-DVB-HC, which was related to the decomposition/ combustion of graphene and the residue of carbonaceous. The extrapolated degradation onset temperatures (T d ) and the temperature of the maximum weight loss rate (T max1 and T max2 ) in Table 3 showed the effect of graphene content on the degradation behavior and thermal stability of the GPNC-IERs.…”
Section: Carbon While the G-bandmentioning
confidence: 99%
“…Recently, graphene has played an important role in nanoscience owning to its exceptional mechanical, electrical, chemical and thermal properties. [18][19][20][21] Its mechanical strength is comparable to that of CNTs and the two-dimensional honeycomb layer of sp 2 -bonded structure has potential applications in many elds as composite materials, energy storage and conversion, sensors and nanoscale electronic components, etc. Recent studies have reported that the scalable production cost of graphene sheets in large quantities could be much lower than CNTs, which might rival the CNTs in many technological applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In condensed matter physics, the application of the derivation methods is also a very efficient tool. In addition, the results obtained in this paper may also lay the groundwork for the further research on graphene networks [28], the structures of some non‐metallic crystals [29] or the carbon nano‐tubes [30] and so on.…”
Section: Potential Applicationmentioning
confidence: 99%